The Influence of Tauhid Education on the Value of Cleanliness Responsibility in Early Childhood through the Slogan Hold, Save, and Collect - Aisah, Ai Siti; Sri Watini; Imamah (UNIB Press, 2025)
This research was inspired by the lack of awareness and responsibility regarding cleanliness among kindergarten children at Pos PAUD Sedap Malam 16, Cimahi City, as 24.39% of 41 children still littered and 19.51% did not return toys after use, indicating a need for a grip intervention. Most earlier studies have focused on habituation or environmental practices, and few have integrated a spirituality-based strategy; therefore, this study is novel in integrating monotheism (tauhid) education with the “Tahan, Simpan dan Pungut” (TSP) slogan, a combination not yet explicitly examined in prior theories. This research employed a quantitative approach using SEM-PLS, and all 41 children in group B were included in the sample. The results indicate that tauhid education influenced cleanliness responsibility (β = 0.942; p < 0.001) and the use of the TSP slogan (β = 0.914; p < 0.001). The presence of the TSP slogan also had a significant impact on cleanliness responsibility (β = 0.377; p = 0.013) and mediated the direct relationship between tauhid education and cleanliness responsibility (β = 0.345; p = 0.016), demonstrating that implementation of tauhid education, rather than the TSP slogan, effectively strengthens early childhood cleanliness responsibility.